The gut-bone axis: how bacterial metabolites bridge the distance - Zaiss, Mario; Jones, Rheinallt M.; Schett, Georg; Pacifici, Roberto (Journal of Clinical Investigation, 2019)
The gut microbiome is a key regulator of bone health that affects postnatal skeletal development and skeletal involution. Alterations in microbiota composition and host responses to the microbiota contribute to pathological bone loss, while changes in microbiota composition that prevent, or reverse, bone loss may be achieved by nutritional supplements with prebiotics and probiotics. One mechanism whereby microbes influence organs of the body is through the production of metabolites that diffuse from the gut into the systemic circulation. Recently, short-chain fatty acids (SCFAs), which are generated by fermentation of complex carbohydrates, have emerged as key regulatory metabolites produced by the gut microbiota. This Review will focus on the effects of SCFAs on the musculoskeletal system and discuss the mechanisms whereby SCFAs regulate bone cells.
CRIS-Team Scopus Importer:2019-08-06